(untitled) (Global Journal of Human-Social Science, 2022)
The study reveals circumstances under which the National Rural Health Mission NRHM program was launched by the Government of India to fulfill the target set out by the United Nation s Millennium Development Goals MDG s It examines the role and functioning of NRHM in delivering basic health care services to rural India It further delineates the role of NRHM in reducing Infant Mortality Rate IMR Maternal Mortality Rate MMR Total Fertility Rate TFR Dengue Mortality Reduction Rate etc The study also highlights the character of NRHM in providing equitable affordable and quality health care services to the rural population particularly the vulnerable groups It was instrumental in creating new institutions decentralizing of services and providing new ideas and resources for health system The study mainly focused on the approaches major planks achievements and evaluation of the NRHM program